When Multipath QUIC meets model predictive control and band sparse network coding: a novel multipathing solution for video streaming over heterogeneous wireless networks - Cao, Yuanlong; Zhang, Haopeng; Jiang, Ming; Jiang, Yirui; Nie, Jinquan (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Multipath Quick UDP Internet Connections (MPQUIC) integrated with network coding offers a promising approach to improving the Quality of Experience (QoE) for video services over heterogeneous wireless networks. However, a significant challenge arises when encoding nodes transmit potentially redundant packets while awaiting decoding acknowledgments (ACKs) from endpoints. This behavior can limit effective transmission rates, thereby degrading real-time streaming performance and user QoE. In this paper, we propose MP2-QUIC, which addresses these challenges through a novel adaptive Model Predictive Control (MPC) framework for MPQUIC that optimizes both congestion window and encoding redundancy parameters via a discrete state transition model. By incorporating operating point linearization and leveraging the Central Limit Theorem, MP2-QUIC effectively enhances the control performance and effective throughput of the model in heterogeneous wireless network environments. MP2-QUIC further employs Band-Sparse Network Coding (Band-SNC) to minimize computational complexity at endpoints, while utilizing queuing theory principles to determine optimal encoded packet quantities. This integrated approach significantly enhances end-user QoE, and the experimental results demonstrate MP2-QUIC’s superior performance compared to existing MPQUIC encoding solutions, yielding a 68.85% reduction in peak decoding overhead and marked improvements in Peak Signal-to-Noise Ratio (PSNR).
Keywords: 4006 Communications Engineering; 40 Engineering; Networking & Telecommunications; Heterogeneous wireless networks; video streaming; network coding; transmission efficiency; QoE